MOST FREQUENT CARP (Cyprinus carpio L.) DISEASES IN PONDS FROM 1994. TO 1998 - Zdravko Petrinec; Milan Božić; A Berc; Ante Jelić (Croatian Journal of Fisheries, 1999)
Fish health monitoring was carried out in the period from 1994. to 1998. for 252 fresh water ponds. Findings about health status depended upon the quality of health control measures such as ichthyotechnic, ichthyosanitary and ichthyohygieni methods. Most frequently diagnosed diseases and their percentages of incidence were: carp erythrodermatytis in 5,82 %, ichthyophtiriasis in 13,51 %, trihodiniasis in 33,568 %, dactylogirosis and gyrodactilosis in 35,75 %, botriocephalosis in 14,99 % and swimbladder inflammation caused by Sphaerospora angulata in 17,77 % examined ponds.